2016
DOI: 10.3390/rs8020135
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of GPM-IMERG and Other Precipitation Products against Gauge Data under Different Topographic and Climatic Conditions in Iran: Preliminary Results

Abstract: Abstract:The new generation of weather observatory satellites, namely Global Precipitation Measurement (GPM) constellation satellites, is the lead observatory of the 10 highly advanced earth orbiting weather research satellites. Indeed, GPM is the first satellite that has been designed to measure light rain and snowfall, in addition to heavy tropical rainfall. This work compares the final run of the Integrated Multi-satellitE Retrievals for GPM (IMERG) product, the post real time of TRMM and Multi-satellite Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
195
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(221 citation statements)
references
References 31 publications
19
195
0
7
Order By: Relevance
“…The IMERG v5 product, with relatively high POD and CSI, showed better performance in precipitation detection of the Huaihe River basin. This was mainly because the GPM combined Instrument (GMI) sensor can capture light precipitation better than the TRMM combined Instrument (TMI) [42]. Additionally, Figure 9 demonstrated the FAR was increased, but the POD and CSI were reduced with increasing rainfall rate for the two satellite precipitation products, suggesting the limited capability of satellite sensors in detecting intense rainfall events [24].…”
Section: Discussionmentioning
confidence: 94%
“…The IMERG v5 product, with relatively high POD and CSI, showed better performance in precipitation detection of the Huaihe River basin. This was mainly because the GPM combined Instrument (GMI) sensor can capture light precipitation better than the TRMM combined Instrument (TMI) [42]. Additionally, Figure 9 demonstrated the FAR was increased, but the POD and CSI were reduced with increasing rainfall rate for the two satellite precipitation products, suggesting the limited capability of satellite sensors in detecting intense rainfall events [24].…”
Section: Discussionmentioning
confidence: 94%
“…A few recent studies have proven that the GPM IMERG products are generally superior to TRMM in several regions, such as the Xinjiang region [30] and the Qinghai-Tibetan Plateau in China [30,31]; Mainland China [33,34]; Guilan, Bushehr, Kermanshah, and Tehran regions in Iran [37]; Far-East Asia [35]; and India [36]. However, in the present study, although the daily precipitation data of both the IMERG final run and TMPA 3B42V7 captured the spatiotemporal variation patterns of rainfall events in the Chindwin River basin in Myanmar, no significant improvements were found in IMERG.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies [31][32][33][34][35][36][37] found that, although 3B42V7 and IMERG products effectively capture the spatiotemporal variations of precipitation in different regions around the world, these estimates still contain considerable errors when compared with ground observations. Given that precipitation inputs are among the most dominant uncertainty sources for hydrological models, satellite precipitation products must be bias-corrected when adopted as the input of a hydrological model for streamflow simulations.…”
Section: Bias-correction For Satellite Precipitation Productsmentioning
confidence: 99%
“…The probability of detection (POD) represents the ratio of the number of precipitation occurrences that are correctly detected by the satellite product (hits) to the number of precipitation occurrences that are observed by the reference data (hits plus misses), which is expressed as a/(a + c). The false alarm ratio (FAR) captures the number of rainfall events that were incorrectly detected, and it can be calculated by the equation b/(a + b) [17]. Table 3.…”
Section: Categorical Verification Metricsmentioning
confidence: 99%